2021
DOI: 10.1002/cam4.3923
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of radiofrequency ablation versus cryoablation in the treatment of single hepatocellular carcinoma: A population‐based study

Abstract: Background Radiofrequency ablation (RFA) is an effective treatment for single hepatocellular carcinoma (HCC), but it is difficult to use against tumors in some locations and often leads to incomplete ablation as a result of the heat‐sink effect. This study was conducted to evaluate the efficacy of cryoablation compared with that of RFA in the treatment of single HCC. Methods This retrospective study was conducted based on the Surveillance, Epidemiology, and End Results (SEER) database. From 2004 to 2015, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Recently, accumulating evidence has revealed that cryoablation (CRA) can trigger antitumor activity by releasing tumor antigens from frozen tumor cells and activating CTLs. However, CRA is limited in effectively treating HCC, compared to other thermal ablations, such as MWA and RFA 2 , 10 , 11 , 12 . Based on our clinical samples, we found PD-L1 + CD11b + cells were significantly increased, especially in MWA, whereas the number of PD-L1 + tumor cells were more increased in CRA than in MWA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, accumulating evidence has revealed that cryoablation (CRA) can trigger antitumor activity by releasing tumor antigens from frozen tumor cells and activating CTLs. However, CRA is limited in effectively treating HCC, compared to other thermal ablations, such as MWA and RFA 2 , 10 , 11 , 12 . Based on our clinical samples, we found PD-L1 + CD11b + cells were significantly increased, especially in MWA, whereas the number of PD-L1 + tumor cells were more increased in CRA than in MWA.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of ablation and checkpoint block inhibitors (CBI), such as anti-PD-1 or anti-CTLA-4 antibodies, can efficiently induce the abscopal effect and increase the prognosis of colorectal cancer, breast cancer, and prostate cancer 8 , 9 . However, some studies have revealed that CRA does not significantly improve the overall survival of HCC patients compared to MWA and radio-frequency-ablation (RFA) 10 , 11 , 12 . Whether CRA or MWA combined with immunotherapy can improve therapeutic efficacy for HCC treatments still needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Heat-based ablation sometimes faces limitations when the tumors are near large blood vessels, bile duct, stomach, or the intestines. Although artificial pneumoperitoneum or ascites can be created to push the stomach or intestines away, the heat-sink effect of large vessels can seriously affect the treatment outcome [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method relies on cyclical freeze–thaw mechanisms, which involve the use of cryoprobes that are cooled using argon gas and then heated with helium gas [ 19 ]. As a result, tumor necrosis is induced through the formation of intracellular ice crystals, which cause damage to the integrity of the cell membranes and lead to the release of their contents into the extracellular space, thereby setting off the body’s immune defenses [ 20 ]. Among the advantages of cryoablation over RFA are its creation of greater ablation zones, the occurrence of less procedural pain and the development of ice balls generated by cryoprobes during the procedure, which allows intraprocedural monitoring [ 18 , 21 ].…”
Section: Locoregional Therapiesmentioning
confidence: 99%